From The Wire to Swedish Socio-crime: police procedural’ s ‘ ’ realism’ ’ and ‘ ’ social criticism’ ’ - Tomić, Janica (2008)
The HBO’ s TV series The Wire has typically been dubbed as one of ‘ ’ The Greatest TV Show You’ ve Never Seen", the "never seen" being both a critique of it’ s insufficient popularity in the USA (most frequent interpretation being that the general public’ s Erwartungshorizont was ill equipped for the experiment with genre, in terms of form as well as different racial and other social issues the series raises), and a reference to the uniqueness of the series’ hybridity (the-cops-and-robbers plot expanding in each season to include a "Balzacian network" of Baltimore city institutions - school system, city authorities, media etc. - changing the genre designations from police to e.g. urban drama). After compiling a generic description of police procedural and the ‘ ‘ realistic’ ’ elements commonly ascribed to the sub-genre in comparison with other crime narratives, the following analysis will discuss how The Wire shifts from the conventions of that sub-genre, as well as from the more general concept of crime genre’ s semantic and syntactic devices. Contextualization of crime, as a feature of The Wire and comparable texts, is further analysed (esp. in The Wire where it develops to such a degree that it becomes the structuring principle, causing the text to transgress the crime genre, and the reception to produce hybrid designations like ‘ ’ urban procedural ’ ’ ). The last section of this paper will draw comparisons with examples of a distinct Swedish tradition of police procedurals that have long been recognized as a ‘ ’ socially critical’ ’ or even as ‘ ’ the socio-crime’ ’ sub-genre (Brönnimann).